International Symposium on Digital Literacy fosters media content awareness - Nor Salwana, Mohammad Idris (2022)
PEKAN, 12 October 2022 - Digital Literacy International Symposium: Media and Information Literacy could nurture the community to handle media content more responsibly and ethically in personal, professional and community activities.